RECOGNITION IDENTIFICATION AND BIOLOGY OF GELECHIDAE (LEPIDOPTERA) IN SOLANACEAE IN DEPARTMENT OF ANTIOQUIA (COLOMBIA) I. SCROBIPALPULA ABSOLUTA (MEIRICK) - VÉLEZ-ANGEL, RAÚL (Revista Colombiana de Entomología, 1988)
A survey of species of Gelechiidae associated with solanaceous plants was carried out in 12 different life zones in the State of Antioquia (Colombia). Scrobipalpula absoluta (Meyr.) was found attacking tomatoes in the municipalities of Bello, Venecia, El Peñol, Marinilla, and Santa Fé de Antioquia. The life cycle was studied under laboratory conditions at an average temperature of 25.3°C and 74.9°/o relative humidity. The results were, as follows: the incubation period was 4 days as an average. Four larval instars were found following Dyar's rule. The mean larval duration was 13.1 days. The pre-pupae it was possible to separate males from females in this stage. Male pupae lived 9.6 days and female pupae 8.8 days. The adult females lived 17.8 days ant the males 16.4 days. Fecundity (total egg number per female) was 226.1. The sex ratio was found to be 1:M: 1.3H. Regarding natural enemies, the braconid Apanteles gelechiidivorus Marsh eas found as a larval parasite. An unidentified ichneumonid and Zatropis sp. (Pteromalidae) emerged from larvae or pupae of hosts collected in the field and reared in the laboratory.